THE DOSE-RESPONSE PHENOMENON ASSOCIATED WITH STRENGTH TRAINING IS INDEPENDENT OF THE VOLUME OF SETS AND REPETITIONS PER SESSION - Evangelista,Alexandre L. (2021)
ABSTRACT Introduction There are few studies on the effectiveness of training models with high volume sets per session in particular muscle groups. Objective The aim of the study was to investigate the effects of different resistance training (RT) repetitions with equalized volumes on muscle adaptations. Methods This study used an experimental design in which forty-seven volunteers underwent 8 weeks of RT after having been distributed randomly into three groups: ten sets of three maximum repetitions (10x3), three sets of ten maximum repetitions (3x10) and five sets of six maximum repetitions (5x6) for each muscular group per training session. Maximum strength (1RM test) and muscle thickness (MT) were evaluated as outcomes. Results A significant main effect (p=0.001) of time on maximum strength was observed for the three groups, but no significance was observed (p>0.05) in time x group interactions. A significant main effect (p=0.001) of time was observed on MT for biceps, triceps and vastus lateralis, without significant differences for time x group interactions. Significant correlations were found between maximum strength and muscle thickness after general statistical analyses for all protocols. Conclusion Improvements in maximum strength and muscle thickness are similar when repetition volumes are equalized through the number of series and repetitions. Level of evidence I; Therapeutic studies, investigation of treatment results.